Filamin-A expression in triple-negative breast cancer and its clinical significance - Abderrahman Ouban (Taylor & Francis Group, 2021)
The quest for discovering novel biomarkers of triple-negative breast cancers (TNBCs) is ongoing. By lacking expression of hormonal receptors, this aggressive subtype of breast cancer presents a clinical dilemma with early recurrence, metastases and poor survival outcome. Filamin-A is a recent novel protein which has proven to play a dual role as an oncogene and a tumour-suppressor in many malignancies. This study analysed the expression of Filamin-A in TNBC cases. Filamin-A was significantly expressed by the majority of the study’s sample, and was correlated with grade, clinical stage and TNM staging. Filamin-A is a versatile protein with numerous interactions with the cytoskeleton components of the tumour cell and with signalling proteins. Its role in modulating chemosensitivity to the chemotherapeutic agent Docetaxel is particularly important, especially in TNBC patients, who have few management options to choose from. This study provides evidence of the clinical significance of Filamin-A in TNBCs, and propose further functional studies to pinpoint the exact function of this protein in this difficult-to-treat subset of breast cancer patients.